Seminal Mnemonics as a Pattern for System Analysis - Neelameghan, A. (Journal of Information and Knowledge, 1970)
The use of Seminal Mnemonics consists in having the same digit or digit group to denote seminally equivalent ideas in whatever subject they may occur even though different terms may be used to denote the ideas in different contexts. S R Ranganathan’s General Theory of Library Classification recommends the use of this device in the design and development of schemes for classification. It has also been found helpful in the actual practice of designing schemes for classification. The denotation of certain groups of ideas by certain numerals is said to have been practised in some ancient traditions, such as that of India and Chaldea. However, the idea of Seminal Mnemonics is often considered something abstract and even beyond the grasp of the average intellect. This has made communicating and teaching about Seminal Mnemonics difficult. As a result, the device is not finding the wide use that it merits. While teaching classification, the two recurring questions about Seminal Mnemonics relate to: (1) The helpfulness of the association of a particular group of ideas with a particular numeral; and (2) The helpfulness of the sequence of ideas derived by this association of a numeral, with an idea. In a class discussion it was found helpful and practicable to consider that (1) The ancient tradition of associating or denoting particular groups of ideas by particular numerals as a means of securing a helpful sequence among these ideas; and (2) The sequence of the ideas thus obtained as representing the sequence of steps generally occurring in planning and designing a system, in systematic thinking, in scientific method, and in problem solving. These points are examined in some detail with illustrative examples from the field of Management of a Quality Control Programme, Postulate-based Method of Classifying, and generalised version of the procedure for problem solving.